2015
DOI: 10.4103/1305-7456.156832
|View full text |Cite
|
Sign up to set email alerts
|

Microshear bond strength evaluation of surface pretreated zirconia ceramics bonded to dentin

Abstract: Objectives:To comparatively assess the micro shear bond strength (MSBS) of dentin bonded surface pre-treated zirconia ceramics.Materials and Methods:Zirconia blocks were sectioned into 50 cubical blocks. The blocks were further categorized into five groups (n = 10 each). Group I: No treatment was performed on zirconia samples; Group II: The zirconia samples were sand-blasted; Group III: Group II + etched with 9.8% of hydrofluoric (HF) acid for 60 s; Group IV: The sandblasted zirconia samples were selectively i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…SIE starts with the application of a heated glass infiltration agent to the zirconia surface, which gives it in an eroded and porous characteristic . By means of thermal cycling, the surface is then transformed into a highly retentive, highly reactive nanoporous surface .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…SIE starts with the application of a heated glass infiltration agent to the zirconia surface, which gives it in an eroded and porous characteristic . By means of thermal cycling, the surface is then transformed into a highly retentive, highly reactive nanoporous surface .…”
Section: Discussionmentioning
confidence: 99%
“…A hindrance to SIE's widespread adoption is that it requires more time, effort and sensitive handling during every step of the technique . Previous studies have reported that the SIE method leads to higher bond strength to zirconia than sandblasting . These findings are probably related to the differences in topography achieved by means of each technique.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations